Semantic meaning of heart in conceptual language system - Madaminova Iroda (Genius Journals, 2022)
This article explains the semantic meaning of heart in the conceptual language system and the following definition of a “concept” is proposed: a concept is a verbalized symbolic image of an “ideal” concept, reflecting the mental representation of native speakers about the “object” of reality, determined by the system of traditions of a given culture, within the boundaries of which it (the concept) is “etymologized” the inner form of the word expressing it.
Keywords: Concept; Semantic Meaning Of Heart; Terminological Distinction; Emotion